Evaluating the Digestibility of Ammonia Fermented (Amofer) Corn Cob Using Different Levels of M21 Decomposer and Urea (In Vitro Study) - Restuti Fitria; Siti Rahmawati Zulaikhah; Novita Hindratiningrum (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2020)
This research aimed to evaluate the addition of M21 Decomposer (MD) and urea (U) on the Dry matter digestibility (DMD) and Organic matter digestibility (OMD) in vitro. There were five treatments and five replicates. The treatments in this study were the addition of MD and U at different levels. namely R0 = Corn cob without amofer/control; R1 = Amofer Corn cob plus 0.04% MD+3% U; R2 = Amofer Corn cob plus 0.06% MD+3% U; R3 = Amofer Corn cob plus 0.04% MD+5% U; and R4 = Amofer Corn cob plus 0.06% MD+5% U. The obtained data were subjected to Analysis of Variance and continued by an Orthogonal Contrast. The result showed that the treatments significantly affected (P<0.05) both DMD and OMD digestibility. The digestibility of amofer corncob was higher than the non-amofer that exhibited 17.982±2.4409% DMD and 26.024±3.009% OMD. The highest DMD and OMD digestibility was observed in R4. i.e.. 24.655±4.858% and 34.276±5.176%. respectively. In conclusion. the best level in the incorporating MD and U is at MD 0.06% and U 5% could improve DMD by 6.673% and OMD by 8.252%.